Diet during Pregnancy and Early Life and Molar Incisor Hypomineralization: A Systematic Review - Mazur, Marta; Corridore, Denise; Jedlinski, Maciej; Ndokaj, Artnora; Straker, Marsha; Guerra, Fabrizio (International Journal of Child Health and Nutrition, 2023)
Introduction: Molar Incisor Hypomineralisation (MIH) is a clinical, highly prevalent worldwide condition described in the early 2000s. Evidence about its aetiology is still missing, and preventive strategies can’t be established. The aim of this study was to systematically review the literature on possible correlations between maternal and infant nutrition during the first thousand days of life and the occurrence of MIH. Methods: Literature searches of free text and MeSH terms were performed using MedLine (PubMed), Scopus and Google Scholar (from 2017 to February 1st, 2023). Results: The search strategy identified 1815 potential articles: 99 from PubMed, 6 from Scopus, and 1710 from Google Scholar. After removing duplicates, papers not meeting the inclusion criteria or being irrelevant, 6 papers were included. They were published between 2019-2022 and were clinical trials or longitudinal studies conducted in Egypt, New Zealand, Turkey, Denmark, Germany and Norway. The sample size was 2005 subjects (mean: 334). All reporting data on MIH was diagnosed according to the European Academy of Paediatric Dentistry criteria. The nutritional exposure variables were: i) malnutrition; ii) vitamin D serum levels in the mother and the child at different stages; iii) celiac disease; iv) the type of infant feeding, such as exclusive breastfeeding and/or type of weaning; v) supplementation with high-dose vitamin D during pregnancy. Conclusion: High-dose vitamin D supplementation during pregnancy may be protective against MIH in children. There is a need for structured epidemiological studies specifically designed to investigate the aetiology of MIH in mother-child cohorts.